ANALISIS KEPUTUSAN PEMBELIAN KONSUMEN THE BODY SHOP - Wisnu Hermawan; Denny Asmara; Sunyoto Sunyoto; Suwarno Suwarno (STMIK Pringsewu, 2023)
The objectives of this study were (1) to determine the effect of green product on purchasing decisions, (2) to determine the effect of green advertising on purchasing decisions, and (3) to determine the effect of green brand image on purchasing decisions. This study used a quantitative approach with an associative design. The population used in this study were consumers of The Body Shop cosmetic products who usually purchase The Body Shop cosmetic products online at The Body Shop's official store. The data collection technique used in this study was questionnaire distribution. Hypothesis testing in this study was carried out using multiple linear regression with the help of SPSS. The results showed that partially, green product affects purchasing decisions with a significance value of 0.000, green brand image affects purchasing decisions with a significance value of 0.001, and green brand image affects purchasing decisions with a significance value of 0.000. Simultaneously, green product, green advertising, green brand image affect purchasing decisions.